Petrogenesis and Geological Structure of Tantan Granitoid in Sungai Manau District, Merangin Regency, Jambi Province - Ariani, Rizky Putri; Utama, Hari Wiki (EKSPLORIUM, 2022)
Tantan granitoids are Late Triassic–Early Jurassic age intrusive rocks that are quite extensive and can be partially found in Sungai Manau Sub-district, Merangin Regency, Jambi Province. Tantan granitoids are found in the Barisan Hills physiography, a magmatic arc line on Sumatra Island. Tantan granitoids are interesting to observe to explain rock formation. The petrographic and XRF analyses can provide insight into the intrusive rock type, its relationship to the tectonic framework, and magmatism. The trend of potential mineral resources can be interpreted based on the granitoid-type approach. The Tantan Granitoid Intrusion has two types of rocks: granite and quartz monzodiorite. Granite and quartz monzodiorite are sub-alkaline magma types, with the granitoid type being I-type metaluminous, which tends to have potential with base metal minerals associated with hornblende minerals from observations or petrographic analysis. Based on the TAS diagram of Na2O+K2O vs. SiO2 shows that the sub-alkaline magma type is a calc-alkaline series type in the K2O vs. SiO2 diagram and a calc-alkaline type in the AFM diagram. This data analysis shows that the tectonic formation of the Tantan Granitoid magma was formed from orogenic results in the form of a Continental Arc. This type can be associated with Meso-Thetic subduction activities against the West Sumatra Sundablock during the Late Triassic–Early Jurassic. Structures in the study area include northwest-southeast trending horizontal faults, including Batang Tantan Fault, Tiangko Fault, Sei Tengko Fault, and Serik Fault, then northeast–southwest trending regional faults, and relatively downward trending faults, namely Serik Fault and Betung Fault. The formation of fault structures is believed to result from subduction tectonic processes during this period.